Features of teaching human anatomy to foreign students - Zinych, O. L.; Hrinivetska, N. V.; Abrosimov, Yu. Yu.; Зінич, Олена Леонідівна; Грінівецька, Наталія Валеріївна; Абросімов, Юрій Юрійович (Запорізький державний медичний університет, 2020)
Demand for higher education in Ukraine is gradually growing. Meeting the needs of the medical community requires more knowledge. In Ukraine higher medical education guarantees quality knowledge acquisition. Despite the complexity of living conditions and the distance from home, students from Ecuador, India and Morocco come to Ukraine for knowledge. The language of study for most of these students is English, but some of them can gain knowledge in Ukrainian. Human anatomy is one of the fundamental disciplines of medicine. In Zaporizhzhia State Medical University this discipline is taught at the Department of Human Anatomy, Operative Surgery and Topographic Anatomy. Almost all lecturers of the Department speak a foreign language. But in the process of teaching there are some difficulties associated with the peculiarities of the student’s nationality, degree of language proficiency, and behavior peculiarities.